2018
DOI: 10.1589/jpts.30.454
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chin tuck exercise using neckline slimmer device on suprahyoid and sternocleidomastoid muscle activation in healthy adults

Abstract: [Purpose] This study investigated the effect of chin tuck exercise (CTE) using a neckline slimmer device on suprahyoid (SH) and sternocleidomastoid (SCM) muscle activation in healthy adults. [Subjects and Methods] We measured activation of the SH and SCM muscles using surface electromyography in 20 healthy adults during head lift exercise (HLE) and CTE using a neckline slimmer device. The order of exercises was randomized and the mean and peak values of each muscle’s activation were assessed. [Results] During … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 7 publications
0
14
0
1
Order By: Relevance
“…In repeated‐measures studies, suprahyoid muscle activation in the CTAR method was mostly assessed only during the isometric component. The sustained chin‐tuck position time was 10 s 18 to 60 s, 15,17 and the rest time between each trial was a few minutes. The participants in the study by Yoon et al 10 also performed 10 repetitions of the isotonic components with the isometric components, and the number of trials of components in repeated‐measures studies ranged from 1 to 5 (Table 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In repeated‐measures studies, suprahyoid muscle activation in the CTAR method was mostly assessed only during the isometric component. The sustained chin‐tuck position time was 10 s 18 to 60 s, 15,17 and the rest time between each trial was a few minutes. The participants in the study by Yoon et al 10 also performed 10 repetitions of the isotonic components with the isometric components, and the number of trials of components in repeated‐measures studies ranged from 1 to 5 (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, recent studies have attempted approaches based on various equipment and methods such as elastic hand-held devices and non-hand-held devices, Theraband, neckline slimmer device and game-based CTAR exercises. 9,[12][13][14][15] Therefore, this study aimed to summarise the methods, protocols, evaluation methods and clinical effects of CTAR exercise reported so far through a systematic review.…”
Section: Introductionmentioning
confidence: 99%
“…Each session lasts nearly 50 min, initiating by 5–7 min of warm-ups and finishing by cool-down, respectively [ 59 ]. In addition, the exercises are initiated by three repetitions holding for 10 s using the Borg scale [ 68 ] and progress to six repetitions, holding for 25 s based on overload principles and individual characteristics [ 59 , 61 ]. If reporting pain during the exercise performance, the subjects can discontinue and rest until pain relief, while moderating the exercises accordingly.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, exercises specifically targeting the trapezius and SA muscles are commonly incorporated into rehabilitation programs to optimize the scapular position and motion [ 69 ]. Recent studies indicated that the specific training of the neck muscles, such as strengthening deep cervical flexor muscles, could reduce neck pain and improve SCM endurance, which is effective in correcting head and shoulder postures [ 68 , 70 ]. Therefore, these exercises are recommended to improve the function of muscles in the neck, shoulder, and thoracic for several painful conditions due to their reduced or altered activation.…”
Section: Methodsmentioning
confidence: 99%
“…Specifinė strategija -pratimai, kuriuos gydytojai taiko rijimo judesiams sustiprinti, pagerinti rijimo laiką. Kai kurie pratimai gali būti atliekami keliomis pakopomis, todėl gali netikti pacientams, turintiems pažinimo sutrikimų [35,36].…”
Section: Pavardėunclassified